Recurrent activating mutations of PPARγ associated with luminal bladder tumors - Natacha Rochel (Nature Portfolio, 2019)
Activation of the PPARγ/RXRα pathway in luminal bladder cancers has mainly been linked to PPARG gene amplifications and activating point mutations in RXRα. Here, the authors identify recurrent PPARγ mutations with similar effects and elucidate the structural basis for this mutational PPARγ activation.